PENGUJIAN APLIKASI GAME PUZZLE INDONESIA BERBASIS ANDROID DENGAN TEKNIK BLACK-BOX TESTING - Hendra, Hendra; Kristianto, Ryan Putranda (ISTEK WIDURI, 2024)
The fast-growing development of technology has brought changes to how individuals carry out their daily lives, one of which is the presence of gadgets. The existence of this technology makes it easy in almost all aspects, both in searching for information, doing activities, and in using applications as a means for learning and entertainment. This paper discusses the process of designing, implementing and testing an Android mobile application with a puzzle game theme. The process of designing and building the application utilizes tools from Figma and Android Studio. The Puzzle Indonesia application adopts the concept of Indonesian culture and aims to serve as a platform for children to gain insight and practice cognitively. The Puzzle Indonesia application can now be downloaded through the Play Store. The application testing was carried out using the Black-Box Testing technique and distributing questionnaires using Likert Scale guidelines. Through this test, it was found that the Black-Box testing technique could be applied well and through the questionnaire an average score of 90.24% was obtained from the 12 respondents involved and there were evaluations from several respondents. ABSTRAKPerkembangan teknologi yang kian berkembang pesat membawa perubahan pada bagaimana suatu individu menjalankan kesehariannya, salah satunya yakni dengan hadirnya gawai. Adanya teknologi tersebut memberikan kemudahan pada hampir semua aspek, baik dalam mencari informasi, beraktivitas, hingga dalam menggunakan aplikasi sebagai sarana untuk belajar dan hiburan. Makalah ini membahas tentang proses perancangan, implementasi, dan pengujian aplikasi mobile android bertemakan permainan puzzle. Proses dalam rancang bangun aplikasi tersebut memanfaatkan tools dari Figma dan Android Studio. Aplikasi Puzzle Indonesia menganut konsep Kebudayaan Indonesia serta bertujuan untuk menjadi wadah bagi anak-anak dalam menambah wawasan serta berlatih secara kognitif. Aplikasi Puzzle Indonesia kini sudah dapat diunduh melalui Play Store. Adapun pengujian aplikasi dilakukan dengan teknik Black-Box Testing dan pembagian kuisoner menggunakan pedoman Skala Likert. Melalui pengujian tersebut, diperoleh bahwa teknik pengujian Black-Box dapat diterapkan dengan baik serta melalui kuisoner didapatkan nilai rata-rata sebesar 90,24% dari 12 responden yang terlibat dan adapun evaluasi dari beberapa responden.